Arabidopsis Calmodulin-Like Proteins, CML15 and CML16 Possess Biochemical Properties Distinct from Calmodulin and Show Non-overlapping Tissue Expression Patterns - Ogunrinde, Adenike; Munro, Kim; Davidson, Alexandra; Ubaid, Midhat; Snedden, Wayne A. (Frontiers in Plant Science, 2017)
Calcium ions are used as ubiquitous, key second messengers in cells across eukaryotic taxa. In plants, calcium signal transduction is involved in a wide range of cellular processes from abiotic and biotic stress responses to development and growth. Calcium signals are detected by calcium sensor proteins, of which calmodulin (CaM), is the most evolutionarily conserved and well studied. These sensors regulate downstream targets to propagate the information in signaling pathways. Plants possess a large family of calcium sensors related to CaM, termed CaM-like (CMLs), that are not found in animals and remain largely unstudied at the structural and functional level. Here, we investigated the biochemical properties and gene promoter activity of two closely related members of the Arabidopsis CML family, CML15 and CML16. Biochemical characterization of recombinant CML15 and CML16 indicated that they possess properties consistent with their predicted roles as calcium sensors. In the absence of calcium, CML15 and CML16 display greater intrinsic hydrophobicity than CaM. Both CMLs displayed calcium-dependent and magnesium-independent conformational changes that expose hydrophobic residues, but the degree of hydrophobic exposure was markedly less than that observed for CaM. Isothermal titration calorimetry indicated two and three calcium-binding sites for CML15 and CML16, respectively, with affinities expected to be within a physiological range. Both CML15 and CML16 bound calcium with high affinity in the presence of excess magnesium. Promoter-reporter analysis demonstrated that the CML16 promoter is active across a range of Arabidopsis tissues and developmental stages, whereas the CML15 promoter activity is very restricted and was observed only in floral tissues, specifically anthers and pollen. Collectively, our data indicate that these CMLs behave biochemically like calcium sensors but with properties distinct from CaM and likely have non-overlapping roles in floral development. We discuss our findings in the broader context of calcium sensors and signaling in Arabidopsis.